(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: Management of emergence agitation (EA) following tonsillectomy with or without adenoidectomy under general anaesthesia in children has been a major challenge for anaesthesiologists.Several medications have been investigated in an attempt to reduce the occurrence and severity of EA. Objectives: The purpose of this study is to determine the effect of premedication with intravenousmidazolam and ketamine on EA following tonsillectomy with or without adenoidectomy under generalanaesthesia in children. Study design: Randomised clinical study. Methods: Sixty children of both sex, American Society of Anaesthesiologists (ASA) physical status I & IIage 5 to 12 years scheduled to undergo elective tonsillectomy with or without adenoidectomy were randomlyassigned into two groups. Patients in group K (n=30) received premedication of intravenous ketamine0.25 mg/kg body weight in 5 ml total volume and in group M (n=30) received premedication 0.1 mg/kgbody weight intravenous midazolam in 5 ml total volume. After completion of surgery patients weretransferred to recovery. Incidences and severity of EA(Paediatric Anaesthesia Emergence Delirium Scale),pain score (Wong-Baker FACES Pain scale) and postoperative nausea and vomiting (PONV) were assessedat admission in the recovery (T0) and in the post anaesthesia care unit (PACU) at 5 min (T5), at 15 min(T15) and at 30 min (T30). Results: Incidences of EA in Group K remained significantly lower than Group M at admission to therecovery and in the PACU at 5 min and 15 min (P<0.05). Severity of EA was significantly lower patientsin Group K than Group M at admission in recovery and in PACU at 5 minute and 15 minute (P<0.05).There were no significant differences in pain scores between two groups. Regarding PONV there was nosignificant difference between two groups. Conclusion: Premedication with ketamine was more effective than midazolam in the prevention of EAfollowing tonsillectomy with or without adenoidectomy in pediatric patients under general anaesthesia. JBSA 2020; 33(2): 55-61